Turbine platform phantom cooling from airfoil film coolant, with purge flow. (September 2019) - Yang, Xing; Liu, Zhao; Liu, Zhansheng; Feng, Zhenping; Simon, Terrence
Highlights: A new cooling source "phantom cooling" was proposed to cool turbine platform. Effects of hole shape and compound angle on phantom cooling were investigated. Combined effects of phantom cooling and purge flow cooling were highlighted. Numerical simulations in predicting platform flow and heat transfer were evaluated. Abstract: Phantom cooling is a new cooling term used in gas turbine cooling designs. It refers to all the second-order or unintentional cooling by various cooling discharges, including leakage, in the turbine passage. In this paper, numerical simulations of phantom cooling on platform surfaces from blade film-cooling injection are performed in a blade linear cascade model. The effects of hole shape and compound angle for the blade pressure and suction side holes on blade platform phantom cooling are studied with various coolant-to-mainstream mass flow ratios ( MFR s) from 2.0% to 4.0%. Purge flow cooling from a 45 deg upstream slot is added to the analysis to investigate the combined cooling performance of phantom cooling and purge flow cooling . Results show that phantom cooling from the blade surface coolant films noticeably helps cooling of the platform, particularly at the junction between the blade pressure surface and the platform, which is usually difficult to cool. Increasing MFR is found to significantly improve phantom cooling performance. Adding compound angle injection to the blade cooling design enhances phantom cooling effectiveness, but shaping the hole exit is detrimental. Generally, a combined cooling scheme with upstream purge flow and phantom cooling from blade surface injection could sufficiently protect the entire platform surface without additional platform discrete hole film cooling. The effectiveness of the combined cooling effect cannot be found by a simple superposition of the two cooling sources because of the interactions between the coolant and secondary flows. It is recommended that accounting for phantom cooling could not only improve cooling design but also save cooling air.